Cultural Dissonance and Identity Confusion: The Mediating Role of Bicultural Integration - Kaya, Selin; Al-Mahmoud, Ahmed; Ahmmed, Badhon (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the mediating role of bicultural identity integration in the relationship between cultural dissonance and identity confusion among bicultural individuals residing in Iraq. Methods and Materials: A descriptive correlational design was employed using a sample of 439 bicultural adults selected based on Morgan and Krejcie’s sample size table. Participants completed standardized self-report instruments measuring cultural dissonance, bicultural identity integration (BII), and identity confusion. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation coefficients, and AMOS-21 for structural equation modeling (SEM). The normality, linearity, multicollinearity, and homoscedasticity assumptions were checked and met. The SEM model included direct, indirect, and total paths, and model fit was evaluated using Chi-square, RMSEA, GFI, AGFI, CFI, and TLI indices. Findings: Cultural dissonance showed a significant positive correlation with identity confusion (r = .52, p < .001), while BII was negatively correlated with both cultural dissonance (r = –.48, p < .001) and identity confusion (r = –.55, p < .001). The structural model demonstrated excellent fit (χ²/df = 1.99, RMSEA = .048, CFI = .96, TLI = .95). Direct paths revealed that cultural dissonance significantly predicted identity confusion (β = .39, p < .001) and negatively predicted BII (β = –.47, p < .001); BII significantly reduced identity confusion (β = –.45, p < .001). The indirect effect of cultural dissonance on identity confusion through BII was significant (β = –.21, p < .001), confirming partial mediation. Conclusion: The results highlight that bicultural identity integration serves as a critical psychological mechanism that buffers the negative impact of cultural dissonance on identity development. Enhancing BII may therefore serve as a valuable strategy in reducing identity confusion among bicultural individuals, particularly in socioculturally complex environments.